Crystalline radical polymerizable composition

JP2025034336APending Publication Date: 2025-03-13MITSUBISHI GAS CHEMICAL NEXT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023140652
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、金型充填性と成形体の機械強度のいずれにも優れる結晶性ラジカル重合性組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034336000001
    Figure 2025034336000001
Patent Text Reader

Abstract

To provide a crystalline radical polymerizable composition excellent in both of mold filling properties and mechanical strength of a molded article.SOLUTION: There is provided a crystalline radical polymerizable composition containing a urethane (meth) acrylate-based radical polymerizable compound, an inorganic filler, a silane coupling agent, and a radical polymerization initiator, wherein the urethane (meth) acrylate-based radical polymerizable compound comprises: a crystalline urethane (meth) acrylate (A); and an amorphous urethane (meth) acrylate (B) which is a hydroxy group-containing (meth) acrylate adduct of a nurate type polyisocyanate of isophorone diisocyanate, and wherein the mass ratio [(A) / (B)] of the urethane (meth) acrylate (A) to the urethane (meth) acrylate (B) is 20 / 80 to 40 / 60, and the content of the silane coupling agents is 0.5 to 3.0 mass% based on the total amount of the crystalline radical polymerizable composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a crystalline radically polymerizable composition. [Background technology]

[0002] Electrical and electronic components used in automobiles, electrical appliances, etc., deteriorate due to the heat they give off. Therefore, metal wiring and metal cases such as aluminum are generally used to dissipate heat and prevent deterioration. In recent years, there has been a demand for improved productivity of the above-mentioned electric and electronic devices, freedom in case shape, and insulation for electric and electronic components, and as a result, metals are being replaced by resin materials. When using a resin material as a material for electric and electronic components, it is necessary to add an inorganic filler to impart thermal conductivity, and therefore thermosetting resins with low viscosity and excellent heat resistance are used as resin materials for electric and electronic components.

[0003] For example, Patent Document 1 discloses a crystalline radically polymerizable composition for electrical and electronic components, which contains a crystalline radically polymerizable compound, an inorganic filler, a silane coupling agent, and a radical polymerization initiator, for the purpose of improving thermal conductivity and ease of handling. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-089871 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, thermosetting resins such as urethane (meth)acrylate resins are used as resin materials for electric and electronic components because they have excellent heat resistance and low viscosity. It is desirable to mold a thermosetting resin composition used for an electric / electronic component at a low pressure in order to reduce the load on the electric / electronic component and not damage the electric / electronic component, but it is necessary to perform molding at a high temperature and high pressure in order to fill the mold. By adjusting the shape of the filler, the fluidity can be increased and the above-mentioned filling property can be improved, but the use of such a filler causes a problem that the strength of the obtained molded body is reduced. Therefore, there has been a demand for a thermosetting resin composition that has excellent fluidity in a mold and excellent strength of the molded body. Therefore, an object of the present invention is to provide a crystalline radically polymerizable composition which is excellent in both mold filling property and mechanical strength of a molded product. [Means for solving the problem]

[0006] The present inventors have found that the above-mentioned problems can be solved by a crystalline radically polymerizable composition that contains two types of urethane (meth)acrylate and a silane coupling agent, the composition and content of which are within specific ranges. That is, the present invention relates to the following. [1] A crystalline radically polymerizable composition containing a urethane (meth)acrylate-based radically polymerizable compound, an inorganic filler, a silane coupling agent, and a radical polymerization initiator, wherein the urethane (meth)acrylate-based radically polymerizable compound is composed of a crystalline urethane (meth)acrylate (A) and a non-crystalline urethane (meth)acrylate (B) which is a hydroxyl group-containing (meth)acrylate adduct of a nurate-type polyisocyanate of isophorone diisocyanate, the mass ratio [(A) / (B)] of the urethane (meth)acrylate (A) to the urethane (meth)acrylate (B) being 20 / 80 to 40 / 60, and the content of the silane coupling agent is 0.5 to 3.0 mass% based on the total amount of the crystalline radically polymerizable composition. [2] The crystalline radically polymerizable composition according to the above [1], wherein the content of the silane coupling agent is 1.0 to 2.0% by mass. [3] The crystalline radically polymerizable composition according to the above [1] or [2], wherein a mass ratio of the urethane (meth)acrylate (A) to the urethane (meth)acrylate (B) [(A) / (B)] is 25 / 75 to 35 / 65. [4] The crystalline radically polymerizable composition according to any one of the above [1] to [3], wherein the silane coupling agent is a (meth)acrylic silane-based silane coupling agent. [5] The crystalline radically polymerizable composition according to any one of the above [1] to [4], wherein the inorganic filler is at least one selected from the group consisting of fused spherical silica and spherical alumina. [6] The crystalline radically polymerizable composition according to any one of the above [1] to [5], which is for use in electric and electronic parts. [7] A molded electric / electronic component obtained by molding the crystalline radically polymerizable composition according to any one of the above [1] to [6]. [8] A method for producing a molded article for an electric / electronic component, comprising molding the crystalline radically polymerizable composition according to any one of the above [1] to [6]. Effect of the Invention

[0007] According to the present invention, it is possible to provide a crystalline radically polymerizable composition which is excellent in both mold filling property and mechanical strength of a molded product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Crystalline radically polymerizable composition] The crystalline radical polymerizable composition of the present invention is a crystalline radical polymerizable composition containing a urethane (meth)acrylate-based radical polymerizable compound, an inorganic filler, a silane coupling agent, and a radical polymerization initiator, in which the urethane (meth)acrylate-based radical polymerizable compound is composed of a crystalline urethane (meth)acrylate (A) and a non-crystalline urethane (meth)acrylate (B) which is a hydroxy group-containing (meth)acrylate adduct of a nurate type polyisocyanate of isophorone diisocyanate, the mass ratio [(A) / (B)] of the urethane (meth)acrylate (A) to the urethane (meth)acrylate (B) is 20 / 80 to 40 / 60, and the content of the silane coupling agent is 0.5 to 3.0 mass% based on the total amount of the crystalline radical polymerizable composition. In the present invention, "(meth)acrylate" refers to at least one selected from the group consisting of "acrylate" and "methacrylate", and "(meth)acrylic" refers to at least one selected from the group consisting of "acrylic" and "methacrylic".

[0009] The "crystalline" compound in the present invention is a compound that has a melting point. The melting point can be confirmed by a thermal analyzer such as a DSC (differential scanning calorimeter) or a TGDTA (thermogravimetric differential thermal analyzer). The melting point of the crystalline compound in the present invention can be confirmed by a thermal analyzer. A compound that does not have a melting point is called an "amorphous" compound.

[0010] The crystalline radically polymerizable composition of the present invention, having the above-mentioned constitution, is excellent in both mold filling property and mechanical strength of molded articles, and is suitable as a molding material for electric and electronic parts. Therefore, among the above-mentioned crystalline radical polymerizable compositions, the present invention also includes a crystalline radical polymerizable composition for use in electric and electronic components. The crystalline radical polymerizable composition of the present invention is preferably a crystalline radical polymerizable composition for use in electric and electronic components. The crystalline radically polymerizable composition of the present invention can be used in low-pressure molding, reducing the load on electrical and electronic components when filling a mold, and the molded product after curing can protect the electrical and electronic components from strong impacts.

[0011] The reason why the crystalline radically polymerizable composition of the present invention, which has the above-mentioned constitution, is excellent in both mold filling property and mechanical strength of a molded product is not clear, but is thought to be as follows. The resin obtained by curing the two kinds of urethane (meth)acrylate radical polymerizable compounds contained in the crystalline radical polymerizable composition of the present invention has a rigid resin skeleton, and the obtained molded article is considered to have excellent strength. Furthermore, since the content of the silane coupling agent is high, it is considered that the silane coupling agent reacts with the hydroxyl group on the surface of the inorganic filler, and when mixed with the radical polymerizable compound, the viscosity becomes low, and the flowability during molding is high. Due to the above-mentioned constitution, it is believed that the crystalline radically polymerizable composition of the present invention is excellent in both mold filling property and mechanical strength of molded articles.

[0012] <Urethane (meth)acrylate radical polymerizable compound> The crystalline radically polymerizable composition of the present invention contains a urethane (meth)acrylate-based radically polymerizable compound, the urethane (meth)acrylate-based radically polymerizable compound being composed of a crystalline urethane (meth)acrylate (A) and a non-crystalline urethane (meth)acrylate (B) which is a hydroxy group-containing (meth)acrylate adduct of a nurate-type polyisocyanate of isophorone diisocyanate, and the mass ratio [(A) / (B)] of the urethane (meth)acrylate (A) to the urethane (meth)acrylate (B) is 20 / 80 to 40 / 60.

[0013] (Urethane (meth)acrylate (A)) The urethane (meth)acrylate (A) is a crystalline urethane (meth)acrylate.

[0014] The urethane (meth)acrylate (A) is not particularly limited so long as it is crystalline, and may be an adduct of a hydroxyl group-containing (meth)acrylate of a polyisocyanate. An "adduct of a polyisocyanate and a hydroxy group-containing (meth)acrylate" is an adduct obtained by forming a urethane bond between the isocyanate group of a polyisocyanate and the hydroxy group (hydroxyl group) of a (meth)acrylate that contains a hydroxy group (hydroxy group-containing (meth)acrylate). The urethane (meth)acrylate (A) may further contain a component made of a polyol or a polyester polyol.

[0015] The polyisocyanate used in the urethane (meth)acrylate (A) may be an aromatic isocyanate compound, an alicyclic isocyanate compound, an aliphatic isocyanate compound, etc., and is preferably at least one selected from the group consisting of an alicyclic isocyanate compound and an aliphatic isocyanate compound, and more preferably both an alicyclic isocyanate compound and an aliphatic isocyanate compound. Also, isocyanate prepolymers modified with polyols are preferably used.

[0016] Examples of the aromatic isocyanate compound include 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, orthotolidin diisocyanate, and 1,4-phenylene diisocyanate. Examples of the alicyclic isocyanate compound include 1,4-cyclohexane diisocyanate and 1,4-cyclohexanediylbis(methylene) diisocyanate. Examples of the aliphatic isocyanate compound include 1,6-hexamethylene diisocyanate, etc. These isocyanate compounds can be used alone or in combination of two or more kinds.

[0017] Of the polyisocyanates, at least one selected from the group consisting of orthotolidin diisocyanate, 1,4-cyclohexane diisocyanate, and 1,6-hexamethylene diisocyanate is preferred, and at least one selected from the group consisting of orthotolidin diisocyanate and 1,6-hexamethylene diisocyanate is more preferred.

[0018] The hydroxy group-containing (meth)acrylate is preferably a hydroxyalkyl (meth)acrylate. Examples of the hydroxyalkyl (meth)acrylate include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and hydroxyphenoxypropyl (meth)acrylate. Hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate are preferred, and hydroxyethyl (meth)acrylate is more preferred.

[0019] When a component consisting of a polyol or a polyester polyol is contained, examples of usable polyols include aliphatic diols and etherified diphenols, and examples of polyester polyols include those obtained by polycondensation of at least one selected from the group consisting of unsaturated acids and saturated acids with at least one selected from the group consisting of aliphatic diols and etherified diphenols.

[0020] (Urethane (meth)acrylate (B)) The urethane (meth)acrylate (B) is an amorphous urethane (meth)acrylate which is a hydroxy group-containing (meth)acrylate adduct of a nurate type polyisocyanate of isophorone diisocyanate.

[0021] "Hydroxy group-containing (meth)acrylate adduct of nurate type polyisocyanate of isophorone diisocyanate" refers to an adduct obtained by forming a urethane bond between the isocyanate group of the nurate type polyisocyanate of isophorone diisocyanate and the hydroxy group (hydroxyl group) of a (meth)acrylate containing a hydroxy group (hydroxy group-containing (meth)acrylate). The urethane (meth)acrylate (B) may further contain a component made of a polyol or a polyester polyol.

[0022] The hydroxy group-containing (meth)acrylate is preferably a hydroxyalkyl (meth)acrylate. Examples of the hydroxyalkyl (meth)acrylate include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and hydroxyphenoxypropyl (meth)acrylate. Hydroxyethyl (meth)acrylate and hydroxypropyl (meth)acrylate are preferred, and hydroxyethyl (meth)acrylate is more preferred. Therefore, the urethane (meth)acrylate (B) is preferably a hydroxyethyl (meth)acrylate adduct of a nurate type polyisocyanate of isophorone diisocyanate.

[0023] When a component consisting of a polyol or a polyester polyol is contained, examples of usable polyols include aliphatic diols and etherified diphenols, and examples of polyester polyols include those obtained by polycondensation of at least one selected from the group consisting of unsaturated acids and saturated acids with at least one selected from the group consisting of aliphatic diols and etherified diphenols.

[0024] The mass ratio [(A) / (B)] of the urethane (meth)acrylate (A) and the urethane (meth)acrylate (B) contained in the crystalline radically polymerizable composition is 20 / 80 to 40 / 60. The mass ratio [(A) / (B)] of the urethane (meth)acrylate (A) to the urethane (meth)acrylate (B) contained in the crystalline radical polymerizable composition is 20 / 80 to 40 / 60, preferably 20 / 80 to 35 / 65, more preferably 20 / 80 to 30 / 70, and even more preferably 25 / 75 to 30 / 70. By containing the urethane (meth)acrylate (A) and the urethane (meth)acrylate (B) in the above-mentioned ratio, the crystalline radical polymerizable composition of the present invention can improve the strength of the molded body and also has good fluidity, resulting in a crystalline radical polymerizable composition that is excellent in both mold filling properties and mechanical strength of the molded body.

[0025] <Other radical polymerizable compounds> The crystalline radically polymerizable composition of the present invention may contain a radically polymerizable compound other than the urethane (meth)acrylate-based radically polymerizable compound. Examples of the radical polymerizable compound other than the urethane (meth)acrylate-based radical polymerizable compound include urethane (meth)acrylates other than the urethane (meth)acrylate (A) and the urethane (meth)acrylate (B), epoxy (meth)acrylates, polyester (meth)acrylates, polyether (meth)acrylates, radical polymerizable monomers, and radical polymerizable prepolymers. Of these, radically polymerizable monomers are preferred. Of the radical polymerizable monomers, those having crystallinity are preferred. Examples of the radical polymerizable monomers having crystallinity include ethoxylated isocyanuric acid triacrylate (melting point: about 50° C.), polyethylene glycol di(meth)acrylate (melting point: 35 to 53° C.), methoxypolyethylene glycol (meth)acrylate (melting point: 33 to 40° C.), behenyl acrylate (melting point: 46° C.), tetramethylpiperidyl methacrylate (melting point: 56 to 60° C.), trimethallyl isocyanurate (melting point: 57 to 60° C.), and the like. Examples of suitable acrylamides include ethyl acetate (melting point 83 to 87°C), diacetone acrylamide (melting point about 56°C), itaconic acid dimethyl ester (melting point 36°C), vinyl stearate (melting point 36°C), N-vinyl carbazole (melting point 67°C), N-methylolacrylamide (melting point 71 to 75°C), acrylamide (melting point 84°C), tolylenediallyl carbamate (melting point 85 to 110°C), maleimide (melting point 93°C), and acenaphthylene (melting point 95°C). Among these, ethoxylated isocyanuric acid triacrylate is more preferable.

[0026] The ratio of the urethane (meth)acrylate radical polymerizable compound to the total of the urethane (meth)acrylate radical polymerizable compound and the radical polymerizable compound other than the urethane (meth)acrylate radical polymerizable compound is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more. There is no upper limit, and it is sufficient as long as it is 100% by mass or less, and it is preferable that it is 100% by mass or less, and only the urethane (meth)acrylate radical polymerizable compound may be contained in the crystalline radical polymerizable composition as the radical polymerizable compound. When the content of the urethane (meth)acrylate resin is within the above range, the mold filling property of the resulting crystalline radically polymerizable composition and the mechanical strength of the molded article can be further improved.

[0027] <Inorganic filler> The crystalline radically polymerizable composition of the present invention contains an inorganic filler. The inorganic filler is preferably at least one selected from the group consisting of calcium carbonate, magnesium carbonate, barium carbonate, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, magnesium oxide, silica, alumina, zinc oxide, mica, aluminum nitride, and boron nitride, more preferably at least one selected from the group consisting of silica and alumina, more preferably silica from the viewpoint of flowability and mold filling property, and even more preferably alumina from the viewpoint of excellent heat dissipation. These may be used alone or in combination of two or more kinds.

[0028] The average particle size of the inorganic filler is preferably 100 μm or less, more preferably 0.01 to 50 μm, from the viewpoints of flowability and strength during molding. The shape of the inorganic filler is preferably spherical from the viewpoints of flowability and mold filling property. Even if a spherical inorganic filler is used, the crystalline radical polymerizable composition of the present invention can obtain a molded product having excellent mechanical strength, and can achieve both strength and mold filling property of the molded product. From the viewpoint of achieving both strength and mold filling properties, the inorganic filler is more preferably at least one selected from the group consisting of fused spherical silica and spherical alumina, and even more preferably fused spherical silica.

[0029] The content of the inorganic filler in the crystalline radical polymerizable composition is preferably 50 to 95 mass%, more preferably 60 to 95 mass%, even more preferably 70 to 95 mass%, still more preferably 75 to 90 mass%, and even more preferably 80 to 90 mass%, based on the total amount of the crystalline radical polymerizable composition. When the content of the inorganic filler is within the above range, it is possible to achieve both mold filling properties and strength of the obtained molded body.

[0030] <Silane coupling agent> The crystalline radically polymerizable composition of the present invention contains a silane coupling agent, and the content of the silane coupling agent is 0.5 to 3.0% by mass based on the total amount of the crystalline radically polymerizable composition. Examples of the silane coupling agent that can be used include epoxysilane-based silane coupling agents, aminosilane-based silane coupling agents, cationic silane-based silane coupling agents, vinylsilane-based silane coupling agents, (meth)acrylic silane-based silane coupling agents, mercaptosilane-based silane coupling agents, and composite silane coupling agents thereof. Among these, (meth)acrylic silane-based silane coupling agents are preferred from the viewpoints of strength, fluidity, and mold filling properties. The molecular weight of the silane coupling agent is preferably 120 to 600, more preferably 150 to 500, and even more preferably 200 to 300, from the viewpoint of lowering the viscosity and increasing the flowability of the crystalline radically polymerizable composition.

[0031] The content of the silane coupling agent in the crystalline radical polymerizable composition is preferably 0.6 to 3.0 mass%, more preferably 0.8 to 3.0 mass%, even more preferably 1.0 to 3.0 mass%, still more preferably 1.0 to 2.0 mass%, and even more preferably 1.0 to 1.5 mass%, relative to the total amount of the crystalline radical polymerizable composition. The content of the silane coupling agent is preferably 3 to 21 parts by mass, more preferably 4 to 20 parts by mass, even more preferably 5 to 20 parts by mass, still more preferably 7 to 20 parts by mass, and even more preferably 7 to 15 parts by mass, relative to 100 parts by mass of the urethane (meth)acrylate-based radically polymerizable compound contained in the crystalline radically polymerizable composition. By setting the content of the silane coupling agent within the above range, a crystalline radically polymerizable composition excellent in both mold filling property and mechanical strength can be obtained.

[0032] <Radical polymerization initiator> The crystalline radically polymerizable composition of the present invention contains a radical polymerization initiator. The radical polymerization initiator contained in the crystalline radically polymerizable composition of the present invention is preferably an organic peroxide.

[0033] Examples of organic peroxides include t-butylperoxy-2-ethylhexyl monocarbonate, 1,1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane, t-butylperoxyoctoate, benzoyl peroxide, methyl ethyl ketone peroxide, acetylacetone peroxide, t-butylperoxybenzoate, dicumyl peroxide, etc. These may be used alone or in combination of two or more. Among these, from the viewpoints of the degree of freedom in molding conditions and storage stability, organic peroxides having a 10-hour half-life temperature of 90° C. or higher are preferred, and dicumyl peroxide is more preferred.

[0034] The content of the radical polymerization initiator in the crystalline radical polymerizable composition is preferably 0.02 to 2 mass %, more preferably 0.05 to 1 mass %, even more preferably 0.1 to 0.7 mass %, and still more preferably 0.1 to 0.5 mass %, relative to the total amount of the crystalline radical polymerizable composition. The content of the radical polymerization initiator is preferably 0.15 to 15 parts by mass, more preferably 0.4 to 8 parts by mass, even more preferably 0.7 to 5 parts by mass, and even more preferably 1 to 4 parts by mass, relative to 100 parts by mass of the urethane (meth)acrylate-based radically polymerizable compound contained in the crystalline radically polymerizable composition. By setting the content of the radical polymerization initiator within the above range, it is possible to obtain a cured product having sufficient mechanical strength as a molding material for electric and electronic parts.

[0035] <Other ingredients> The crystalline radically polymerizable composition of the present invention may contain, as other components, a polymerization inhibitor, a colorant, a release agent, a reinforcing material, a thermoplastic resin, a flame retardant, etc., within the scope of not impairing the effects of the present invention, and it is preferable that the composition contains at least one selected from the group consisting of a polymerization inhibitor and a colorant.

[0036] Examples of polymerization inhibitors include quinones such as hydroquinone, monomethyl ether hydroquinone, toluhydroquinone, di-t-4-methylphenol, monomethyl ether hydroquinone, phenothiazine, t-butylcatechol, parabenzoquinone, and pyrogallol; 2,6-di-t-butyl-p-cresol, 2,2-methylenebis(4-methyl-6-t-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butanol; phenolic compounds such as ethane; piperidine-1-oxyls such as 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-oxo-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl, 4-carboxy-2,2,6,6-tetramethylpiperidine-1-oxyl, and 2,2,6,6-tetramethylpiperidine-1-oxyl, and quinones are preferred. By using a polymerization inhibitor, thickening during filling during molding can be suppressed, and a urethane (meth)acrylate resin composition with low melt viscosity can be obtained. These may be used alone or in combination of two or more.

[0037] The content of the polymerization inhibitor in the crystalline radical polymerizable composition is preferably 0.001 to 0.05 mass %, more preferably 0.003 to 0.03 mass %, and even more preferably 0.005 to 0.02 mass %, based on the total amount of the crystalline radical polymerizable composition. The content of the polymerization inhibitor is preferably 0.007 to 0.035 parts by mass, more preferably 0.02 to 0.20 parts by mass, and even more preferably 0.035 to 0.15 parts by mass, based on 100 parts by mass of the urethane (meth)acrylate radically polymerizable compound. By setting the content of the polymerization inhibitor within the above range, thickening during filling into a mold can be suppressed, and a crystalline radically polymerizable composition having a low melt viscosity can be obtained.

[0038] The colorant is preferably carbon black. The content of the colorant in the crystalline radical polymerizable composition is preferably 0.01 to 1 mass % relative to the total amount of the crystalline radical polymerizable composition, more preferably 0.03 to 0.5 mass %, even more preferably 0.05 to 0.3 mass %, and still more preferably 0.05 to 0.2 mass %.

[0039] As the release agent, fatty acid-based release agents, fatty acid metal salt-based release agents, mineral-based waxes, etc., which are generally used for thermosetting resins, can be used, and fatty acid metal salt-based release agents, which have excellent resistance to heat discoloration, are preferred. Examples of the release agent include stearic acid, stearates, paraffin wax, etc., with stearates being preferred. Examples of the stearates include zinc stearate, aluminum stearate, and calcium stearate, and zinc stearate is preferred. The release agents may be used alone or in combination of two or more. As the mold release agent, an external mold release agent such as a type that is sprayed or applied to the mold or a molding material containing a mold release agent can be used as required. The content of the release agent in the crystalline radical polymerizable composition is preferably 8 mass % or less, more preferably 5 mass % or less, even more preferably 3 mass % or less, and even more preferably 2 mass % or less, based on the total amount of the crystalline radical polymerizable composition. The release agent may not be included, and from the viewpoints of increasing adhesion between the resin and the inorganic filler and increasing the fluidity and strength of the molded body, it is preferable that the release agent is not included.

[0040] The reinforcing material preferably includes glass fibers. Examples of glass fibers include E glass (alkali-free glass for electrical use), C glass (alkali-containing glass for chemical use), A glass (acid-resistant glass), S glass (high-strength glass), etc., which are made from silicate glass or borosilicate glass, and these can be used in the form of long fibers (rovings), short fibers (chopped strands), or milled fibers. Furthermore, these glass fibers can also be used after surface treatment. By using a reinforcing material, a cured product having excellent strength characteristics and dimensional stability can be obtained.

[0041] Examples of the thermoplastic resin include polystyrene, acrylic resin, polyvinyl acetate, saturated polyester, and styrene-butadiene rubber.

[0042] As the flame retardant, halogen-based, phosphorus-based, nitrogen-based, and composite organic flame retardants, as well as inorganic flame retardants such as metal hydroxides, antimony-based, red phosphorus-based, silicone-based, and borate can be used. Furthermore, these flame retardants can be additive-type flame retardants or reactive-type flame retardants that react with the resin and are incorporated into the resin skeleton. These flame retardants can be used alone or in combination of two or more.

[0043] <Method for producing crystalline radically polymerizable composition> The crystalline radically polymerizable composition of the present invention is preferably obtained by a production method in which a urethane (meth)acrylate-based radically polymerizable compound, an inorganic filler, a silane coupling agent, a radical polymerization initiator, and any other components are blended, thoroughly and uniformly mixed using a mixer, blender, etc., and then kneaded using a heat-pressurizable kneader, extruder, etc. The obtained kneaded product (crystalline radically polymerizable composition) is preferably granulated, pulverized, and molded into a granulated product, granular product, powder, or other shape.

[0044] [Electrical and electronic component molded body and its manufacturing method] The molded article of an electric / electronic component of the present invention is an electric / electronic component molded article obtained by molding the crystalline radically polymerizable composition. Therefore, the electric / electronic component molded article of the present invention is preferably obtained by a method for producing an electric / electronic component molded article by molding the crystalline radical polymerizable composition, and the method for producing an electric / electronic component molded article is also included in the present invention.

[0045] As a method for molding the crystalline radically polymerizable composition in the method for producing molded electric and electronic components, a known method for molding a thermosetting composition can be used. The crystalline radical polymerizable composition of the present invention has good mold filling properties and is therefore suitable for low pressure molding. Therefore, by using the crystalline radical polymerizable composition, the load on the electric / electronic component during mold filling can be reduced. In addition, the electric / electronic component molded body of the present invention can be obtained by any molding method. Specific molding methods include injection molding, injection compression molding, transfer molding, compression molding, and melt-heat molding methods such as hot melt molding. Among these, the injection molding method using an injection molding machine and the transfer molding method using a transfer molding machine are preferred, with the injection molding method being more preferred from the viewpoint of molding in a short period of time, and the transfer molding method being more preferred from the viewpoints of being able to mold many molded articles at once and of being able to mold molded articles with complex shapes. The temperature of the crystalline radical polymerizable composition when injected into a mold in injection molding is preferably 60 to 130° C., and the temperature of the mold is preferably 130 to 190° C. The pressure of the crystalline radical polymerizable composition is preferably 0.1 to 10 MPa. The temperature of the mold during injection into the mold in transfer molding is preferably 130 to 190°C, and the pressure of the crystalline radical polymerizable composition is preferably 0.1 to 10 MPa. The molding conditions in the above ranges are preferable because they reduce damage to electrical and electronic components. In particular, the crystalline radical polymerizable composition of the present invention can be molded at a lower pressure, which can further reduce damage to electrical and electronic components. Furthermore, the electric / electronic component molded article of the present invention is a molded article obtained by molding the crystalline radically polymerizable composition, and therefore has excellent mechanical strength and can protect the electric / electronic component from strong impact. EXAMPLES

[0046] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. Measurements and evaluations in the examples were carried out by the following methods.

[0047] <Melt viscosity> The melt viscosity of the crystalline radically polymerizable compositions obtained in the Examples and Comparative Examples was measured as follows. The material was placed in a capillary viscometer (BMC viscometer manufactured by Sanki Sangyo Co., Ltd.) and melted at 90°C for 10 minutes. The shear rate was then increased to 125 s -1 The piston was lowered so that the shear stress was measured when the mixture was discharged through a Φ4 mm die. The melt viscosity (Pa s) was calculated from the obtained shear stress.

[0048] <Spiral flow (evaluation of mold filling properties)> The spiral flow of the crystalline radically polymerizable compositions obtained in the Examples and Comparative Examples was evaluated as follows. Based on EIMS T-901, the resin flow length was measured using a mold with a spiral curved groove of Archimedean spiral with a diameter of 3 mm and a semicircular cross section, and a transfer molding machine (MF-O 37, manufactured by Marushi Co., Ltd.). The mold temperature was 165°C, the material was filled with a filling pressure of 4 kN, and the flow length (cm) was measured after curing for 3 minutes. The larger the flow length value, the better the mold filling ability.

[0049] <Flexural strength (evaluation of mechanical strength) and flexural modulus> The bending strength and bending modulus of elasticity of the molded articles obtained by molding the crystalline radically polymerizable compositions obtained in the Examples and Comparative Examples were measured in accordance with JIS K 6911 as follows. A transfer molding machine (MF-O 37, manufactured by Marushichi Co., Ltd.) was used to obtain a molded body measuring 80 mm in length, 4 mm in height, and 10 mm in width. The molded body thus obtained was left for 24 hours in an environment of 23°C and 50% RH, after which a bending test was carried out using a universal testing machine (Autograph AG-50KNB·R, manufactured by Shimadzu Corporation) at a crosshead speed of 2 mm / min to determine the bending strength (MPa) and bending modulus (GPa). The higher the bending strength value, the better the mechanical strength.

[0050] <Raw materials> The raw materials used in the examples and comparative examples are as follows. (Radical polymerizable compound) Crystalline urethane methacrylate (A1): 2-hydroxyethyl methacrylate adduct of 1,6-hexamethylene diisocyanate Amorphous urethane acrylate (B1): 2-hydroxyethyl acrylate adduct of nurate type polyisocyanate of isophorone diisocyanate (T1890 / 100, manufactured by Evonik Industries AG) Amorphous acrylate: Bisphenol A type epoxy resin modified with terminal methacrylate (Inorganic filler) Fused spherical silica (amorphous silica, average particle size 24 μm, manufactured by Nippon Steel Chemical & Material Co., Ltd.) (Silane coupling agent) Methacrylsilane-based silane coupling agent (3-methacryloxypropyltrimethoxysilane, KBM-503, Shin-Etsu Chemical Co., Ltd.) (Radical polymerization initiator) Dicumyl peroxide (Percumyl D-40, NOF Corporation) (Other Ingredients) Polymerization inhibitor: Parabenzoquinone (PBQ, manufactured by Seiko Chemical Co., Ltd.) Colorant: Carbon black (CB40, manufactured by Mitsubishi Chemical Corporation)

[0051] <Production of Crystalline Radical Polymerizable Composition> Examples 1 to 4 and Comparative Examples 1 to 4 The raw materials were mixed in the ratio (parts by mass) shown in Table 1 and uniformly kneaded using a kneader capable of pressurizing, heating and cooling to obtain a crystalline radically polymerizable composition. Table 1 shows the evaluation results.

[0052] [Table 1]

[0053] From Table 1, the crystalline radical polymerizable composition of the embodiment has a large spiral flow length value and a large bending strength value of the molded article. Therefore, it is found that the crystalline radical polymerizable composition of the embodiment has good mold filling property and also has excellent mechanical strength. From this, the crystalline radical polymerizable composition of the present invention can be used for low pressure molding, and can reduce the load on the electric / electronic components when filling the mold, and the molded article after curing can protect the electric / electronic components from strong impact. Therefore, the crystalline radical polymerizable composition of the present invention is suitable as a molding material for electric / electronic components.

Claims

1. A crystalline radically polymerizable composition comprising a urethane (meth)acrylate-based radically polymerizable compound, an inorganic filler, a silane coupling agent, and a radical polymerization initiator, the urethane (meth)acrylate radical polymerizable compound comprises a crystalline urethane (meth)acrylate (A) and a non-crystalline urethane (meth)acrylate (B) which is a hydroxyl group-containing (meth)acrylate adduct of a nurate type polyisocyanate of isophorone diisocyanate; a mass ratio of the urethane (meth)acrylate (A) to the urethane (meth)acrylate (B) [(A) / (B)] is 20 / 80 to 40 / 60; A crystalline radically polymerizable composition, the content of the silane coupling agent being 0.5 to 3.0% by mass based on the total amount of the crystalline radically polymerizable composition.

2. The crystalline radically polymerizable composition according to claim 1, wherein the content of the silane coupling agent is 1.0 to 2.0% by mass.

3. 2. The crystalline radically polymerizable composition according to claim 1, wherein the mass ratio of the urethane (meth)acrylate (A) to the urethane (meth)acrylate (B) [(A) / (B)] is 25 / 75 to 35 / 65.

4. The crystalline radically polymerizable composition according to claim 1 , wherein the silane coupling agent is a (meth)acrylic silane-based silane coupling agent.

5. 2. The crystalline radically polymerizable composition according to claim 1, wherein the inorganic filler is at least one selected from the group consisting of fused spherical silica and spherical alumina.

6. The crystalline radically polymerizable composition according to claim 1, which is for use in electric and electronic parts.

7. 7. A molded electric / electronic component obtained by molding the crystalline radically polymerizable composition according to claim 1.

8. A method for producing a molded article for an electric / electronic component, comprising molding the crystalline radically polymerizable composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Crystalline radical-polymerizable composition for electric / electronic components, electric / electronic component molding prepared using the composition, and method for producing the electric / electronic component molding

    JP2019089871A